Impact of patient: donor HLA disparity on reduced-intensity-conditioned allogeneic stem cell transplants from HLA mismatched unrelated donors for AML: from the ALWP of the EBMT - Loke, J; Labopin, M; Craddock, C; Niederwieser, D; Cornelissen, J; Afansayev, B; Jindra, P; Maertens, J; Blaise, D; Boriskina, K; Gramatzki, M; Ganser, A; et al. (Bone marrow transplantation, 2021)
Patients with acute myeloid leukaemia (AML) who lack a matched sibling or unrelated donor commonly undergo transplantation from a donor matched at 9/10 HLA-A, -B, -C, -DRB1, -DQB1 alleles, and it is unclear if a specific locus mismatch is preferable to any other. We therefore studied 937 patients with AML in complete remission transplanted using a reduced intensity conditioning regimen from an unrelated donor mismatched at a single allele. In a multivariate analysis, patient age, adverse karyotype and patient cytomegalovirus (CMV) seropositivity were correlated with decreased leukaemia free survival (LFS) and overall survival (OS). There was no significant difference in LFS or OS between patients transplanted from donors mismatched at HLA-A, -B, -C or -DRB1 in comparison to a HLA-DQB1 mismatched transplant. In a multivariate analysis, patients transplanted with a HLA-A mismatched donor had higher rates of acute graft-versus-host disease (GVHD) and non-relapse mortality (NRM) than patients transplanted with a HLA-DQB1 mismatched donor. Patient CMV seropositivity was associated with an increase in NRM and acute GVHD and reduced LFS and OS, regardless of donor CMV status. For CMV seropositive patients lacking a fully matched donor, alternative GVHD and CMV prophylaxis strategies should be considered.
Keywords: Hematopoietic Stem Cell Transplantation; akutní myeloidní leukemie; Retrospective Studies; lokální recidiva nádoru; retrospektivní studie; Leukemia, Myeloid, Acute; Graft vs Host Disease; transplantace hematopoetických kmenových buněk; Unrelated Donors; nemoc štěpu proti hostiteli; Humans; lidé; Neoplasm Recurrence, Local; nepříbuzný dárce